种免充气轮胎 (2018)
本发明提出种免充气轮胎，沿轮胎径向由外向内依次包括设置有低滚阻、高抓着力花纹的橡胶胎面，与橡胶胎面硫化成体的基部胶，以及对橡胶胎面起支撑作用的弹性支撑体，其特征在于：弹性支撑体包括与轮辋相接触的内承压环，与基部胶贴合的外承压环，以及位于内承压环和外承压环之间的中部支撑体；外承压环的周向环体内部设有第轴向通孔，第轴向通孔的轴向截面为圆形或弓形圆弧或椭圆形或边数大于等于6的多边形的其中种，且沿圆周方向均匀分布，使得车辆轮轴通过弹性支撑体的第轴向通孔将载荷均匀离散化传递至地面，得到压力分布比较均匀的接地印痕，提高轮胎的接地性能和承载性能。 The invention provides an inflation-free tire. The inflation-free tire sequentially comprises a rubber tire tread with patterns which have low rolling resistance and high grip strength, base rubber which is vulcanized into a whole with the rubber tire tread and an elastic support body achieving a support effect on the rubber tire tread from outside to inside in the radial direction of the tire. The inflation-free tire is characterized in that the elastic support body comprises an inner pressure bearing ring making contact with a rim, an outer pressure bearing ring attached to the base rubber and a middle support body located between the inner pressure bearing ring and the outer pressure bearing ring; first axial through holes are formed in a ci